Impact of a new sampling buffer on faecal haemoglobin stability in a colorectal cancer screening programme by the faecal immunochemical test. Issue 4 (July 2017) - Grazzini, Grazia; Ventura, Leonardo; Rubeca, Tiziana; Rapi, Stefano; Cellai, Filippo; Di Dia, Pietro P.; Mallardi, Beatrice; Mantellini, Paola; Zappa, Marco; Castiglione, Guido
Abstract : Haemoglobin (Hb) stability in faecal samples is an important issue in colorectal cancer screening by the faecal immunochemical test (FIT) for Hb. This study evaluated the performance of the FIT-Hb (OC-Sensor Eiken) used in the Florence screening programme by comparing two different formulations of the buffer, both in an analytical and in a clinical setting. In the laboratory simulation, six faecal pools (three in each buffer type) were stored at different temperatures and analysed eight times in 10 replicates over 21 days. In the clinical setting, 7695 screenees returned two samples, using both the old and the new specimen collection device (SCD). In the laboratory simulation, 5 days from sample preparation with the buffer of the old SCD, the Hb concentration decreased by 40% at room temperature (25°C, range 22–28°C) and up to 60% at outside temperature (29°C, range 16–39°C), whereas with the new one, Hb concentration decreased by 10%. In the clinical setting, a higher mean Hb concentration with the new SCD compared with the old one was found (6.3 vs. 5.0 µg Hb/g faeces, respectively, P <0.001); no statistically significant difference was found in the probability of having a positive result in the two SCDs. Better Hb stability was observed with the new buffer under laboratory conditions, but no difference was found in the clinical performance. In our study, only marginal advantages arise from the new buffer. Improvements in sample stability represent a significant target in the screening setting.